Monocyte Tissue Factor Expression Is Enhanced in Women who Smoke and Use Oral Contraceptives - Hölschermann, Hans; Terhalle, Helma-Meta; Zakel, Ute; Maus, Ulrich; Parviz, Behnoush; Tillmanns, Harald; Haberbosch, Werner (Thrombosis and Haemostasis, 1999)
The association between use of oral contraceptives (OCs) and increased risk of thromboembolic disease has been firmly established. This risk increases when use of OCs is combined with cigarette smoking. The cellular mechanism favoring an hypercoagulable state under these behaviours is not known. Circulating monocytes are potent activators of the coagulation cascade through their ability to synthesize procoagulant tissue factor (TF). In the present study we report that monocyte TF expression is increased in women who use OCs and smoke.We studied monocyte TF expression in 4 groups of healthy pre-menopausal women (n = 15 each): (1) non-smoking OC non-users, (2) nonsmoking current OC users, (3) smoking OC non-users and (4) smoking OC users. TF expression was assessed on both mRNA and protein levels in unstimulated and LPS-stimulated cells. Transcriptional activation of the TF gene was assessed by analysis of the transcription factor NF-κB and its inhibitor molecule IκBα. Monocyte TF generation was significantly higher in OC users than in women who did not use OCs. Enhanced monocyte TF generation was also observed in smoking women when compared to non-smokers. Strongest monocyte TF expression occurred in women with combined smoking and use of OCs. The enhanced TF expression in monocytes from women using OCs or smoking was based on an increased TF gene transcription following activation of NF-κB. Experiments on cultured monocytes/macrophages demonstrated enhanced IκBα degradation in the presence of estradiol, suggesting that a direct hormone effect is responsible for the observed increase in monocyte TF expression.This study demonstrates that use of OCs and smoking is associated with an increase in monocyte TF expression in pre-menopausal women. Aberrant TF expression by blood monocytes may favour intravascular clotting activation in women with OC therapy. The further enhancement of TF activity observed in women who smoke and use OCs may explain the synergistic effect of smoking on risk of thromboembolic events associated with contraceptive use.
Keywords: Tissue factor; monocytes; oral contraception; smoking